PENGARUH MODEL GAME BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MURID PADA MATA PELAJARAN IPAS - Anggun Leony; Indah Yunitasari; Angga Setiawan (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Critical thinking skills are essential competencies in 21st-century learning. However, students' critical thinking skills in Natural and Social Sciences (IPAS) remain relatively low due to teacher-centered learning and a lack of innovative models. While prior studies heavily rely on digital games, research on non-digital Game-Based Learning (GBL) models in elementary schools is still limited. This study aimed to determine the effect of a non-digital GBL model using the 'Pos Environment Damage Challenge' media on the critical thinking skills of fifth-grade students in IPAS subjects. This research employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design using intact classes. The sample consisted of 36 fifth-grade students divided into an experimental class (n=19) and a control class (n=17). Data were collected through multiple-choice tests that passed validity and high reliability tests. Data analysis involved independent sample t-tests and N-Gain tests via SPSS 27.0. The results showed that the average critical thinking score of the experimental class significantly increased from 48.00 to 82.53, whereas the control class only shifted from 49.18 to 50.12. The independent sample t-test obtained a significance value of 0.000 < 0.05, indicating that the GBL model significantly affected students’ critical thinking skills. The critical analysis confirms that the non-digital GBL model stimulates higher-order thinking skills through contextual problem-solving and peer interaction while minimizing digital cognitive overload. It concludes that the GBL model successfully enhances students' critical thinking without digital dependency.